(untitled) (PANGEEA, 2025)
Şard is a rural village belonging Ighiu commune, located in the central part of Alba County. In almost 1000 years of existence, the village names and place names in the area have significant changes. These changes reflect the historical development of the area has seen many important events. The study of place names can lead to an explanation of events that took place in the village and surrounding area.